Opioid, gabapentinoid, and nonsteroidal anti‐inflammatory medication use and the risks of atrial fibrillation and supraventricular ectopy in the Multi‐Ethnic Study of Atherosclerosis. Issue 9 (17th June 2020) - Harding, Barbara N.; Wiggins, Kerri L.; Jensen, Paul N.; McKnight, Barbara; Psaty, Bruce M.; Heckbert, Susan R.; Floyd, James S.
Abstract: Purpose: Opioids, gabapentinoids, and nonsteroidal anti‐inflammatory drugs (NSAIDs) may have adverse cardiovascular effects. We evaluated whether these medications were associated with incident clinically detected atrial fibrillation (AF) or monitor‐detected supraventricular ectopy (SVE), including premature atrial contractions (PACs) and supraventricular tachycardia (SVT). Methods: We used data from the Multi‐Ethnic Study of Atherosclerosis (MESA), a cohort study that enrolled 6814 Americans without clinically detected cardiovascular disease in 2000 to 2002. At the 2016 to 2018 examination, 1557 individuals received ambulatory electrocardiographic (ECG) monitoring. Longitudinal analyses investigated time‐varying medication exposures at the first five exams (through 2011) in relation to incident clinically detected AF through 2015 using Cox proportional hazards regression models. Cross‐sectional analyses investigated medication exposures at 2016 to 2018 examination and the risk of monitor‐detected SVE using linear regression models. Results: The longitudinal cohort included 6652 participants. During 12.4 years of mean follow‐up, 982 participants (14.7%) experienced incident clinically detected AF. Use of opioids, gabapentinoids, and NSAIDs were not associated with incident AF. The cross‐sectional analysis included 1435 participants with ECG monitoring. Gabapentinoid use was associated with an 84% greater average frequency of PACs/hour (95% CI, 25%‐171%) and a 44% greater average number of runs of SVT/day (95% CI, 3%‐100%). No associations were found with use of opioids or NSAIDs in cross‐sectional analyses. Conclusions: In this study, gabapentinoid use was associated with SVE. Given the rapid increase in gabapentinoid use, additional studies are needed to clarify whether these medications cause cardiovascular complications.